2020
DOI: 10.1200/jco.19.01726
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Breast Cancer Treatment on Employment: Results of a Multicenter Prospective Cohort Study (CANTO)

Abstract: PURPOSE Adverse effects of breast cancer treatment can negatively affect survivors’ work ability. Previous reports lacked detailed clinical data or health-related patient-reported outcomes (PROs) and did not prospectively assess the combined impact of treatment and related sequelae on employment. METHODS We used a French prospective clinical cohort of patients with stage I-III breast cancer including 1,874 women who were working and ≥ 5 years younger than legal retirement age (≤ 57 years) at breast cancer diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 45 publications
8
85
1
Order By: Relevance
“…This effect seems to be even more significant in BC survivors, given the physical and psychological comorbidities derived from the disease impact and the administered treatments. 2,3 However, our results were confirmed regardless of the effect of age, suggesting that WA is impaired in BC survivors independently of age. Other direct effects indicated that age decreases EA levels and increase EC values.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This effect seems to be even more significant in BC survivors, given the physical and psychological comorbidities derived from the disease impact and the administered treatments. 2,3 However, our results were confirmed regardless of the effect of age, suggesting that WA is impaired in BC survivors independently of age. Other direct effects indicated that age decreases EA levels and increase EC values.…”
Section: Discussionsupporting
confidence: 48%
“…These results are consistent with most of the research that indicates that BC patients present lower RTW rates, especially after chemotherapy. [1][2][3] Mean differences in WA attending to work status seem to corroborate these results. In this way, we did not find differences in WA of the total sample in employed workers and self-employed conditions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Along with the morbidity of the disease itself, these side effects can impair the physiological and psychological wellness of patients, leading to limitations in their abilities to execute daily activities and participate in social events (Campbell et al, 2012;Shapiro, 2018;Zaidi et al, 2017). In addition, long-term sequelae associated with BC and its treatment, such as anxiety and depression, fatigue, chronic pain, cognitive impairment and peripheral neuropathy, are known to reduce physical, mental and emotional capacity (Bjerkeset et al, 2020;Colombino et al, 2020;De Iuliis et al, 2015;Dumas et al, 2020;Hedayati et al, 2012;Landeiro et al, 2018;Lundh et al, 2014;Rivera et al, 2018;Wefel et al, 2014;Zomkowski et al, 2018). Deterioration in the sense of physical and emotional well-being, and limitations in the functional capacity of patients with BC, negatively affects their quality of life and ability to work (Zaidi et al, 2017).…”
mentioning
confidence: 99%
“…Breast cancer (BRCA) whose mortality rate ranks second among female malignancies is one of the most common malignancy in women worldwide [1][2][3]. On the basis of the latest global cancer statistics, there was almost 2.1 million newly diagnosed breast cancer patients in 2018, amount to nearly one forth women cancer cases [1].…”
Section: Introductionmentioning
confidence: 99%